2014
DOI: 10.1007/978-81-322-1777-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinvasive and Neurotropic Human Respiratory Coronaviruses: Potential Neurovirulent Agents in Humans

Abstract: In humans, viral infections of the respiratory tract are a leading cause of morbidity and mortality worldwide. Several recognized respiratory viral agents have a neuroinvasive capacity since they can spread from the respiratory tract to the central nervous system (CNS). Once there, infection of CNS cells (neurotropism) could lead to human health problems, such as encephalitis and long-term neurological diseases. Among the various respiratory viruses, coronaviruses are important pathogens of humans and animals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
285
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 259 publications
(312 citation statements)
references
References 114 publications
4
285
0
10
Order By: Relevance
“…MERS-CoV is one of the human corona viruses that include also five other strains: SARS-CoV, HCoV-OC43, HCoV-229E, HCoV-NL-63, and HCoV-HKU1. Although corona viruses are generally known for causing respiratory illness, both clinical and experimental studies have demonstrated their strong tropism to the CNS [9][10][11][12][13][14][15]. SARS-CoV infection induced in mice model results in neuronal death without encephalitis [16].…”
Section: Discussionmentioning
confidence: 99%
“…MERS-CoV is one of the human corona viruses that include also five other strains: SARS-CoV, HCoV-OC43, HCoV-229E, HCoV-NL-63, and HCoV-HKU1. Although corona viruses are generally known for causing respiratory illness, both clinical and experimental studies have demonstrated their strong tropism to the CNS [9][10][11][12][13][14][15]. SARS-CoV infection induced in mice model results in neuronal death without encephalitis [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the human airways, HCoV infection may lead to the disruption of the nasal epithelium [250] and, although they bud and are released mostly on the apical side of the epithelial cells, a significant amount of viruses is also released from the basolateral side [251]. Thus, although HCoV infections are, most of the time, restricted to the airways, they may under poorly understood conditions pass through the epithelium barrier and reach the bloodstream or lymph and propagate towards other tissues, including the CNS [33,38,208,252]; this was also suggested for other respiratory viruses that can reach the human CNS, namely, RSV [8,53] [14,220,[252][253][254][255][256]] to manipulate the innate immunity and to disseminate to other tissues, including the CNS, where they may be associated with other type of pathologies, especially in immunocompromised individuals as it was observed for murine cytomegalovirus (MCMV) [257,258]. Moreover, persistently-infected leukocytes [252] may serve as a reservoir and vector for neuroinvasive HCoV [245].…”
Section: Possible Mechanisms Of Hcov Neuroinvasivenessmentioning
confidence: 99%
“…These viruses have also been associated with lower respiratory tract illness in children, elders, and immunodeficient individuals (Falsey et al, 2002;Fouchier et al, 2004;Woo et al, 2005;Gerna et al, 2006). HCoV-229E and HCoV-OC43 may lead to central nervous system infection since viral RNAs are detected in the brain of some patients (Arbour et al, 2000;Desforges et al, 2014).…”
Section: Introductionmentioning
confidence: 99%